The access database for the Zletovo mine, Republic of Macedonia - Tasev, Goran; Serafimovski, Dalibor; Mitreski, Kosta (Stef92 Technology, Sofia, Bulgaria, 2018)
Organization of the Access database of the Zletovo lead-zinc deposit Eastern Macedonia represents the first attempt of this paper authors to synthesize geological exploration data of this ore bearing locality in one professional database available for the interested parties. Ours experience in organization of similar databases for other metal deposits such are Bucim, Borov Dol, Kadiica, Sasa etc., gave us the necessary knowledge and experience to construct quality Access database for the Zletovo deposit. The Zletovo has been classified as a sub-volcanic hydrothermal lead-zinc ore deposit. The main ore minerals are galena and sphalerite. They occur in very distinct structures, microstructures and textures, which often enclose sulphosalt mineral phases. The most common of them being bournonite, boulangerite, proustite and luzonite. This paper focuses on efforts we made to organize Microsoft Access database with the most representative data for this particular deposit in the Republic of Macedonia. At the very beginning, with the software package “Microsoft Access” we have organized database with information of the most important geological, metallogenic and economic features of the deposit. The database was adapted for simple and sophisticated querying of particular deposit features and allows edition of reports and a geographic display of the queried information. Major data that completed database for the Zletovo deposit are: the deposit belongs to the famous Kratovo-Zletovo ore district, it is at the industrial production stage under exploitation concession of the Bulmak company with proved reserves of 9.8 Mt of lead and zinc with 7.59% Pb and 2.44% Zn, mineralization/rocks part of the database showed the mineralization age (relative 16.4-13.6 Ma; absolute 16 Ma) and host rock age (relative 28.4 - 23.03 Ma; absolute 27 Ma, K/Ar method) with main host lithology consisting of pyroclastite and pyroclastic rocks, ignimbrite, wellded tuff, andesite and dacite, economic parameters were dominated by the fact that of proved mineral reserves of 9.8 Mt (as of 2007 and combined lead-zinc metal potential of 704 700 t ; 502 200 t Pb and 202 500 t Zn), also on the comments section we stressed out that its metallogeny is related to Tertiary calk-alkaline magmatism (predominantly Miocene) where mineralization is in dacite ignimbrite comlex and volcanosedimentary suite while ore bodies are in veins.
Keywords: Zletovo lead-zinc deposit, Access database, reserves, economy